Analysis of risk factors of low cardiac output syndrome after pericardiectomy for tuberculous constrictive pericarditis: A retrospective study - Shuangshuang Yan; Jing Guo; Shuzhen Wang; Lijuan Zhang; Li Zhang; Qiuyu Xiao; Qian Li; Zhengkai Zhao; Lijian Cheng; Feng Xiong (Indian Heart Journal)
Objective: Low cardiac output syndrome (LCOS) is the leading cause of death after cardiac surgery. Studies have shown that 24% of postoperative mortality in patients undergoing pericardiectomy is attributed to LCOS. It is necessary to explore the risk factors of LCOS after pericardiectomy in patients with tuberculous constrictive pericarditis (CP). Methods: Patients undergoing pericardiectomy for tuberculous CP were included in the study. The personal and clinical data of these patients with LCOS and without LCOS were collected and compared. Logistic regression analyses were conducted to identify the risk factors of postoperative LCOS. ROC curve analysis was used to check the accuracy of each risk factor to predict LCOS. Results: A total of 175 patients with tuberculous CP were included in this study, of which 35 cases developed LCOS postoperatively, resulting in an incidence rate of 20%. The independent predictors of LCOS were preoperative NYHA class III/IV, decreased left ventricular mass index (LVMI), and hypoalbuminemia in these patients (p < 0.05). When albumin (ALB) < 30.35 g/L, it had the highest diagnostic value in predicting postoperative LCOS, with sensitivity and specificity of 59.4% and 86.9%, respectively (p < 0.01). Conclusions: For patients with tuberculous CP, preoperative NYHA class III/IV, lower LVMI, and hypoalbuminemia are independent risk factors for LCOS following pericardiectomy. Clinically, these risk factors should be identified as early as possible, and early pericardiectomy should be performed when the patient's cardiac function remains well-preserved to avoid the occurrence of cardiac cachexia, myocardial atrophy and severe hepatic insufficiency.